Urejanje prometa v Sloveniji iz vidika varstva okolja - Plevnik, Aljaž (Urbani izziv, 1998)
The article summarises the proposed chapter on traffic in the National programme for environmental protection. The main theme focuses on the suggested goals and measures to reach sustainable development in Slovenia. The goals and measures are derived from the current situation and traffic development trends and their influence on the environment, from international guidelines and the current slovene policies.
Keywords: ecology; ekologija; environmental protection; promet; prostorski razvoj; prostorsko planiranje; regionalno planiranje; Slovenia; Slovenija; spatial planning; varstvo okolja